Tokyo: Reconsiderations on Fear and Urban Monstrosity - A. Balboa, Rafael (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2015)
The monster figure can work to construct a metaphor of the configuration of some contemporaneous cities and how they are being constructed to us. This paper proposes to reconsider Tokyo as a paradigm of diverse urban fears and monstrosities in different times of history. First, this text recognizes a cosmogonical and mythological monstrosity, which was, subsequently, embodied in different disasters that would utterly change the morphology of the city. With a city devastated almost in its entirety during World War II, a new simulated monstrosity would appear, more like fiction, hand by hand with the technological and media advances where the monster would go from a consumer figure to one consumable. One last urban monstrosity is recognized in the more contemporaneous architecture, based on the Metabolism movement in the sixties, and that during postmodernity would become the discordant and mutant collection of its parts. This text seeks to explain this recent monstrosity, creating an analogy of the extended body through the prothesis and the possibility of continuous mutation that it offers. Finally, we find a dynamic figure in the monster metaphor, one capable of regenerating the different forces that form and deform our cities.